Modernizing for performance: Do leadership, service quality, and remuneration drive employee performance in Indonesia’s tax administration? - Aji, Seno (Journal of Economics and Business Letters, 2025)
This study tests whether leadership (X1), service quality (X2), and remuneration (X3) are associated with employee performance (Y) in a modernized public-sector setting. Using a quantitative explanatory design, we surveyed all 103 employees of KPP Madya Jakarta Barat (Section Heads, Functional Tax Auditors, Account Representatives, and Operational Staff). Constructs were measured via structured questionnaires; item–total (corrected) validity and Hoyt reliability confirmed sound measurement (α Leadership = 0.89; Service Quality = 0.925; Remuneration = 0.876; Performance = 0.928). Assumption checks included normality (CR skew/kurtosis within ±2.58), residual autocorrelation (Durbin–Watson in the no-autocorrelation band), and visual inspection for heteroskedasticity (scatterplots). Pearson correlations and simple regressions indicated that Service Quality → Performance (β = 0.429; R² = 0.184; p < 0.001) and Remuneration → Performance (β = 0.501; R² ≈ 0.251; p < 0.001) are positive and statistically significant, while Leadership → Performance is not (β = 0.083; R² = 0.007; p = 0.405). Results align with the human-capital and performance-management view that better service systems and incentive architectures lift frontline outcomes, whereas instruction-heavy, paternalistic leadership—common in legacy bureaucracies—may not translate into measurable performance unless it also reallocates decision rights and empowers initiative. Managerial implications include codifying decision rights, strengthening technology/assurance/security cues in service delivery, and making recognition and promotion criteria transparently contingent on service outcomes. Limitations include single-office scope, self-report measures, and potential ceiling effects; future work should test simultaneous/mediated models across offices and link perceptions to behavioral performance traces.